Increasing Critical Thinking Skills Through Natural Science Learning Based on the Integration of Guided Inquiry with Numbered Heads Together - Syafaren, Alaniyah; Yustina, Yustina; Mahadi, Imam; Vebrianto, Rian (FKIP-Universitas Riau, 2019)
Process of science learning stresses on giving students direct experience to develop their competence. Therefore, teachers are required to be creative and innovative to improve students’ critical thinking. Accordingly, there is a need for a research on “The science learning based on guided inquiry integration with Numbered Heads Together (NHT) toward critical thinking skill”. This research aim to figure out of influence of the science learning based on guided inquiry integration with NHT. This research is a quasi-experimental study, with design